1983
DOI: 10.1111/j.1439-0329.1983.tb00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the pine wood nematode, Bursaphelenchus xylophilus from pine and balsam fir1

Abstract: The pine wood neiTi.itode, Bursaphelenchus xylophilus was found on baLsani iir in Minnesota and Wisconsin but was .ipparently not the primary cause of tree mortality. Unlike li. xylophilus from pine, adult females from hals.im fir had mucronate tails similar to those of /i, mueronatus.However, B. xylophilus from balsam fir mated with B. xylophilus from pine and not with B. mueronatus. The balsam fir isolate of B. xylophilus was pathogenic on (greenhouse grown balsam fir sccdlinj^s and did not kill Scots or red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Inoculation of the nematodes on seedlings tend to give variable results and pathogenicity may vary considerably between isolates oí Bursaphelenchus xylophilus (Wingfield et al, 1983;Mamiya & Enda, 1979;Panesar & Sutherland, 1989). Species of host tree seedlings react differently to the inoculation of the nematodes.…”
Section: Discussionmentioning
confidence: 98%
“…Inoculation of the nematodes on seedlings tend to give variable results and pathogenicity may vary considerably between isolates oí Bursaphelenchus xylophilus (Wingfield et al, 1983;Mamiya & Enda, 1979;Panesar & Sutherland, 1989). Species of host tree seedlings react differently to the inoculation of the nematodes.…”
Section: Discussionmentioning
confidence: 98%
“…Variation in the shape of the female tails, from round, digitate to mucronate has been detected in PWN isolates from Continental Portugal (Penas et al, 2004;Fonseca et al, 2008a;Penas et al, 2008). Mucronate tailed females of PWN have also been reported in Japan and North America (Wingfield et al, 1983;Bolla & Boschert, 1993). Furthermore, most of the morphometric data (Table 2) are within the range of other B. xylophilus isolates previously described (Mamiya & Kiyohara, 1972;Nickle et al, 1981;Mota et al, 1999;Fonseca et al, 2008a;Penas et al, 2008).…”
mentioning
confidence: 98%
“…4 (1989) mucronated tail. The r form conforms to the taxonomic description of B. xylophilus (Nickle et al, 1981) while the m form is similar to the mucronated B. xylophilus that Wingfield et al (1983) found in Minnesota.…”
Section: Introductionmentioning
confidence: 58%
“…In general, the two r form nematodes isolated from pines in Alberta and Missouri were found to be more pathogenic to lodgepole pine seedlings than two m form nematodes isolated from other conifers in Quebec, as shown by greater seedling mortality, shorter interval between inoculation and seedling death, and higher nematode numbers in stems. Wingfield et al (1983) also recorded high mortality of Scots pine and red pine (P. resinosa Ait.) seedlings inoculated with r form PWNs from pine species, but none with m form PWNs from balsam fir.…”
Section: Lodgepole Pine Mortalitymentioning
confidence: 94%
See 1 more Smart Citation